Propulsion systems for hybrid vehicles - Miller, John M. 1949- (Institution of Engineering and Technology, 2010)
The following topics are dealt with: hybrid vehicles; hybrid power plant specifications; electric drive system; power electronics; AC drives; drive system control; hybrid vehicle characterization; energy storage technologies; and automated electrified transportation.
Previous edition: 2004.